2014
DOI: 10.3727/215517913x672254
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Skeletal Myoblast Sheet Therapy for Porcine Myocardial Infarction without Increasing Risk of Arrhythmia

Abstract: Safety concerns of ventricular tachyarrhythmia have arisen from some clinical trials of autologous skeletal myoblast (SkM) injection therapy. This study examined the effect and safety of SkM sheet therapy in a pig model of chronic myocardial infarction. Minipigs underwent LAD occlusion using a balloon catheter for 2 h, followed by reperfusion. After 28 days, 12 SkM sheets were transplanted onto the infarcted myocardium (sheet group n = 8); the same number of cells was also injected into the myocardium (injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As above, the cell sheet method provided good transplantation efficiency with a high engraftment rate, so we chose the tissue‐engineered cell sheet as the cell transplantation method. The regenerative therapy using skeletal myoblast sheets for heart failure is an established therapy in humans (Sawa et al ., ) and many preclinical studies have been done (Terajima et al ., ; Memon et al ., ). These studies reported induction of neovascularization, suppression of fibrosis and improvement of cardiac function.…”
Section: Discussionmentioning
confidence: 98%
“…As above, the cell sheet method provided good transplantation efficiency with a high engraftment rate, so we chose the tissue‐engineered cell sheet as the cell transplantation method. The regenerative therapy using skeletal myoblast sheets for heart failure is an established therapy in humans (Sawa et al ., ) and many preclinical studies have been done (Terajima et al ., ; Memon et al ., ). These studies reported induction of neovascularization, suppression of fibrosis and improvement of cardiac function.…”
Section: Discussionmentioning
confidence: 98%
“…6 The second important lesson is that conventional needle-based intramyocardial injections have several limitations, including random distribution of cells, stress-induced cell damage 7 and, possibly, induction of arrhythmias. 8,9 Since cardiac surgery provides the unique opportunity of a direct control over the heart, several studies have assessed the effects of replacing multiple intramyocardial injections by the epicardial delivery of a cellularized patch and, overall, their results support the superiority of the latter approach with regard to cell survival, [10][11][12][13] reduction of fibrosis, [12][13][14] increase in angiogenesis [12][13][14] and improvement of function. 10,[12][13][14][15] Additional advantages of the patch-based approach include strengthening of the infarcted wall which may contribute to limit adverse remodelling 16 and provision of a template for cells to proliferate and secrete their own matrix to which they can anchor.…”
Section: Introductionmentioning
confidence: 98%
“…In most cases, cells are injected directly into the myocardium in several areas; these multiple intramyocardial punctures induce infl ammation and result in isolated clusters which may slow conduction of electrical impulses and set the stage for reentries; this hypothesis is actually supported by the observation that cells injected into the myocardium cause more arrhythmias than when they are delivered through the systemic route (Fukushima et al 2007 ). The additional fi nding that the epicardial delivery of a cell-loaded patch is also less arrhythmogenic than when the same cells are directly injected into the myocardium (Terajima et al 2014 ) strengthens the role of the cell delivery modalities in the pathogenesis of arrhythmias. Finally, if allogeneic cells are to be used, a possible immune rejection and the attendant infl ammation can further contribute to this complication.…”
Section: Arrhythmiasmentioning
confidence: 92%